IMPROVING STUDENTS READING SKILL IN UNDERSTANDING FUNCTIONAL PROCEDURE AND REPORT TEXTS THROUGH SCANNING TECHNIQUES AT JUNIOR HIGH SCHOOL - St Darmin (Universitas Muhammadiyah Makassar, 2021)
This study aims to improve the skills of understanding the meaning of context in procedure and report functional texts through the scanning reading technique of class IX SMP Negeri 9 Makassar. This research approach, which is descriptive. The design or model of this research is Action Research. The subjects of the study were 23 students of class IX SMP Negeri 9 Makassar State Vocational High School. Data collection is done through observation, documentation, and test techniques. Data analysis techniques, namely quantitative descriptive analysis and qualitative descriptive analysis. The results showed that scanning reading techniques can improve students' ability to understand the meaning of context in procedure and report functional texts are very high and increase from the low category to high with the average value of the first cycle is 56.52 and increases in the second cycle to 82.82. Changes and improvements also appear in the achievement of learning completeness from 21.73% in the first cycle to 100% in the second cycle. The scanning reading technique can increase student activity. In the first cycle, the activity of students was categorized as less and increased in the second cycle to be a very active category. Student interest and motivation increases in understanding procedure and report functional texts, on average students focus attention on learning to understand functional procedure and report texts, the average student is active in learning to understand functional procedure and report texts, and the average value of students from aspects of knowledge and psychomotor reach KKM.